Successful Transplantation of Lungs From an Uncontrolled Donor After Circulatory Death Preserved In Situ by Alveolar Recruitment Maneuvers and Assessed by Ex Vivo Lung Perfusion. Issue 4 (30th January 2016) - Valenza, F.; Citerio, G.; Palleschi, A.; Vargiolu, A.; Fakhr, B. Safaee; Confalonieri, A.; Nosotti, M.; Gatti, S.; Ravasi, S.; Vesconi, S.; Pesenti, A.; Blasi, F.; et al.
Abstract : We developed a protocol to procure lungs from uncontrolled donors after circulatory determination of death (NCT02061462). Subjects with cardiovascular collapse, treated on scene by a resuscitation team and transferred to the emergency room, are considered potential donors once declared dead. Exclusion criteria include unwitnessed collapse, no‐flow period of >15 min and low flow >60 min. After death, lung preservation with recruitment maneuvers, continuous positive airway pressure, and protective mechanical ventilation is applied to the donor. After procurement, ex vivo lung perfusion (EVLP) is performed. From November 2014, 10 subjects were considered potential donors; one of these underwent the full process of procurement, EVLP, and transplantation. The donor was a 46‐year‐old male who died because of thoracic aortic dissection. Lungs were procured 4 h and 48 min after death, and deemed suitable for transplantation after EVLP. Lungs were then offered to a rapidly deteriorating recipient with cystic fibrosis (lung allocation score [LAS] 46) who consented to the transplant in this experimental setting. Six months after transplantation, the recipient is in good condition (forced expiratory volume in 1 s 85%) with no signs of rejection. This protocol allowed procurement of lungs from an uncontrolled donor after circulatory determination of death following an extended period of warm ischemia. Abstract : The authors describe the feasibility of a novel, in situ lung preservation strategy developed to procure lungs from uncontrolled donors after circulatory determination of death. See the editorial from Egan onpage 1051 .